Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

7p-(3p+4)= -2 (2p-1)+10

Sagot :

meli25
7p ( -3p +4) = -2 ( 2p - 1) + 10

so ima do one part first okay.

7p x -3p = -21p

7p x 4 = 28p

so now we put it as a equation. so you have now
-21p +28p = -2 (2p -1) +10

so ima do the second part.
-2 x 2p = -4p
2 x 1 = 2

so now you have -21p + 28p = -4p + 2 + 10

so im going to put all like terms together.

28p - 21p = 7p

7p = -4p + 2 + 10
+4p  +4p

11p = 2 + 10
 
 11p = 12                 
         11 

p = 12/11 *it's your answer

Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.